Analysis of Basic Basketball Technical Skills in PERBASI Basketball Athletes in Makassar City - Suwardi (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
This study aims to analyze the level of basic basketball technical skills (dribble, passing, and shooting) in PERBASI Makassar City athletes using the Johnson Basic Basketball Skills Test. The quantitative descriptive research method involved 20 senior male athletes (aged 18-25 years) from the PERBASI Makassar main team as purposively selected participants. The test instruments included: dribble test (zig-zag 10x), passing test (wall pass 30 seconds), and shooting test (self-pass field goal 30 seconds). The testing procedure was carried out at the PERBASI Makassar basketball court in October 2025 with 2 trials per test, the average value was taken for analysis. Data were analyzed using descriptive statistics (mean, SD, skill category). The results showed an average dribble of 8.45 seconds (good category), passing 28.2 throws (very good category), and shooting 12.3 successful shots (sufficient category). Overall, the athletes' basic technical skills were in the good category (composite score 79.6%), with strength in passing and weakness in shooting. High individual variation in shooting (CV=18.4%) indicates inconsistent shooting accuracy. The study concluded that PERBASI Makassar athletes have good general mastery of basic techniques, but require specific strengthening of shooting accuracy to increase competitiveness at the national level.